Brief communication: efficacy and safety of the dolutegravir/lamivudine dual therapy in antiretroviral treatment-experienced Chinese people living with HIV - Zhenyan Wang; Junyang Yang; Lin Wang; Jiangrong Wang; Yinzhong Shen; Jun Chen; Tangkai Qi; Jianjun Sun; Wei Song; Yang Tang; Shuibao Xu; Li Liu; et al. (AIDS Research and Therapy)
Abstract This study aimed to evaluate the efficacy and safety of dolutegravir plus lamivudine (DTG/3TC) in antiretroviral treatment (ART)-experienced people living with HIV (PLWH). A total of 303 PLWH in Shanghai, China, who switched from triple ART to DTG/3TC between January 2019 and June 2022, with a minimum ART duration of 6 months, were retrospectively enrolled. More than 95% of PLWH maintained viral suppression with no significant changes in CD4 counts 12 months after switching. Patients transitioning from non-tenofovir (TDF)-based regimens demonstrated more pronounced improvements in lipid profiles, while those previously on TDF-based regimens showed greater enhancements in bone metabolism.